Take the First-Person Perspective to Become Dementia-Friendly: The Use of 360° Video for Experiencing Everyday-Life Challenges With Cognitive Decline - Morganti, Francesca; Palena, Nicola; Savoldelli, Paola; Greco, Andrea (Frontiers in Psychology, 2020)
The nowadays spread of dementia reveals an emergency not limited to the medical issues but that comprehends its social dimension as well. Accordingly it is necessary to promote a perspective change about the disease that supports a more inclusive view of people with dementia. To ensure this, the Dementia Friendly Communities have been recently developed. Notwithstanding, to deal with dementia people in an inclusive way is not always effortless, because of the misknowledge about how they perceive everyday contexts and react in everyday situations. We asked 170 individuals (aged between 13 and 75) to “put themselves in the shoes of a person with dementia” for a few minutes, through the use of a 360 ° video, and to try to experience how from the first-person perspective feels like going to have shopping. Before and after the experience participants expressed their opinion about the needs and the autonomies which are deemed to be granted to a person with dementia. Results revealed the social perspective changes after having experienced firsthand how living with dementia could be like. A deeper comprehension about how to live with dementia is like appeared as accomplished and participants’ beliefs about dementia needs and daily autonomies were modified after the experience. It is possible to conclude that, through the change of perspective, people are more willing to be inclusive towards people with dementia as whish for Dementia Friendly Community approach, although a wider formative intervention on how to be really inclusive seems to be still requested.